Melting graft wound syndrome - Shiou-Mei Chen; Jen-Hung Yang; Sung-Jen Hung; Chien-Hsing Wang; Yung-Hsiang Hsu (Wolters Kluwer Medknow Publications, 2017)
Melting graft wound syndrome is characterized by progressive epidermal loss from a previously well-taken skin graft, healed burn, or donor site. It may result in considerable morbidity and require prolonged treatment. We report a 23-year-old flame-burned patient with second- to third-degree burns involving more than 70% of the total body surface area, whose condition was complicated with septic shock. The patient presented with erosions and ulcers occurring on previously well-taken skin graft recipient sites over both legs and progressive epidermal loss on donor sites over the back. The patient's presentation was compatible with the diagnosis of melting graft wound syndrome, and we successfully treated the patient with debridement and supportive treatment.